Innovative agriculture in Ethiopia: public insights on its arrangements. Issue 3 (3rd April 2022) - Tarekegne, Chalachew
ABSTRACT: This study explores whether the arrangement for innovative agriculture is fulfilled in the Ethiopian context as perceived by key stakeholder groups, district-level experts, development agents (DAs), and smallholder farmers. A structural–functional analysis framework was used to guide our assumptions. Quantitative and qualitative methods of data collection and analysis were applied. Our findings revealed weak structural elements and poor functional activities arrangements in the zone and significant differences among key stakeholder groups, district-level experts, DAs, and farmers' perceptions. Particularly, grassroots-level participants (DAs and farmers) enumerated several factors for poor implementation of innovative agriculture in their locality: poor coordination, shortage of competent human resources, budget constraints, and poor infrastructure, among others. To implement innovative agriculture that can benefit the smallholder farming community, therefore, Ethiopia needs to strengthen the arrangements of structural elements and functional activities at the grassroots levels.